Sea water whirlpool spa as a source of Legionella infection - Dijana Tomic Linsak; Darja Kese; Dalibor Broznic; Darija Vukic Lusic; Arijana Cenov; Milan Moric; Ivana Gobin (IWA Publishing, 2021)
Bacterial pneumonia caused by the inhalation of aerosols contaminated with Legionella spp. is also known as Legionnaires' disease. In this study, we report a case of pneumonia caused by Legionella pneumophila sg.1 in a 58-year-old man who visited a sea water-filled whirlpool within a hotel and spa complex. The patient's Legionella urine antigen test was positive for L. pneumophila sg.1. During the field study, samples were taken from both the outdoor and indoor sea water-filled pools. Samples from the whirlpool were culture positive for L. pneumophila sg.1. Typing results indicated sea water isolate belonged to Sequence type ST82 and Allentown/France MAb subgroup. In vitro experiments showed that L. pneumophila strains are able to survive within sea water up to 7 days, and survival time is prolonged with sea water dilution. Also, our results indicate that L. pneumophila Allentown strain was the most resistant to adverse conditions in sea water with the highest values of DT50 (420 min) and DT90 (1,396 min). The possible source of infection was adding potable water for filling up the whirlpool. The survival of the L. pneumophila in additionally conditioned sea water should be considered in a further study. HIGHLIGHTS Sea water in spa resorts may act as an environmental reservoir for Legionella spp.; Sea and brackish water are suitable media for the survival of the Legionella pneumophila.; In vitro experiments show that most Legionella spp. can survive in sea water up to 7 days.; L. pneumophila Allentown strain shows better survival ability in seawater compared to other strains.; The possible source of infection was filling up the whirlpool with potable water.;